Pancasila sebagai Sistem Etika - Arya Wibawa Atmanegara; Ayunda Cinta Dinanti; Utama, Muhammad Daffa Adika; Randika Aryasatya Adipermana; Salman Sahid Sabiq; Sulthan Ariq Haikal; Yayang Furi Furnamasari (Indo-MathEdu Intellectuals Journal, 2024)
Pancasila and ethics are intertwined because they both teach positive values. Pancasila ethics are based on Pancasila values, such as divinity, humanity, unity, populism, and justice. From these values, the Pancasila ethical system emerged which serves as a guideline for individual behavior in social life in Indonesia. The Pancasila ethical system continues to be developed in its implementation, so that every step and effort of the Indonesian people in achieving common goals can be directed correctly. This research uses a qualitative approach with literature study methods or literature research. This research focuses on written works, including research results that have been published. The main source of data for this article is the results of research published through google scholar. Data collection is carried out using the keywords "Pancasila" and "ethical system". Data analysis was carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawn. The findings of this research are that the application of Pancasila as an ethical system is moral guidance that can be actualized into concrete actions, involving various aspects of life. Pancasila as a state ethical system also needs to be applied as the foundation of morality and state integrity that is hidden in every individual citizen so that he can master spiritual and mental attitudes in community life. Critical-analytical studies are also needed to find out if the element of subjectivity is fanatical and avoidable